Silica mesoporosa sba-15 modificada com ácido etilenodiaminotetracético – síntese, caracterização e adsorção de cátions (ca2+ e mg2+) em água potável - Marques, Vanessa da Silva Bezerra (Universidade Federal Rural do Semi-Árido, 2019)
Unsatisfactory management, changes in consumption parameters and drought undermine many parts of the world to survive in the face of drinking water shortages (MARINOSKI; RUPP; GHISI, 2018) and the quality of drinking water must be evaluated for its adequate consumption. Water that has hard hardness can lead to the accumulation of mineral deposits in pipes and appliances that use water on a regular basis, affecting the performance and the useful life of these items. In addition, in the presence of soaps, the fatty acids formed an insoluble precipitate with calcium ions, making it difficult to foam and cleaning, as well as other problems generated by the high content of Ca2 + and Mg2 + ions present in water (HAGE & CARR, 2012). The objective of this work was to study the removal of Ca2 + and Mg2 + ions using a mesoporous silica of SBA-15 type functionalized with ethylenediaminetetraacetic acid (SBA-15C) and compared with its pure matrix (SBA-15 B). This adsorbent was tested in solution of Ca 2+ and Mg 2 + ions at a concentration of 250 mg.L-1 as pH = 9, varying the temperature at 25 40 and 50 ° C and the adsorbent medium (SBA-15, EDTA-SBA-15 ). The mesoporous materials were synthesized by the hydrothermal method and characterized by TG / DTG, XRD and BET; the adsorption results showed removal of Ca2 + and Mg2 + ions in a short time (approximately 5 min) and pH adjustment showed better removal results and the application of mesoporous materials of the SBA-15 type showed promising for the reduction of hardness of residual or potable water.
Keywords: SBA-15; EDTA; Adsorção; Íons Ca2+ e Mg2+; SBA-15; EDTA; Adsorption; Ions; Ca2+ e Mg2+; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA